The green technology financing scheme (GTFS) in Malaysia: revealing the competency trap - Zaharudin, Mohd Azlan (2017)
This research aims to understand the transition of established entrepreneurial firms into sustainable entrepreneurship ventures in Malaysia using a competency based perspective. The research considers established entrepreneurial firms attempts to acquire green technology financing. By observing a green technology financing scheme (GTFS) a competency trap is identified that constrains established entrepreneurial firms, regardless of their excellent financing track record and previous business success in other ventures. Utilising Rasmussen et al.’s (2011, 2014) evolutionary entrepreneurial competency framework, the research examines how established entrepreneurial firms develop the entrepreneurial competencies to overcome this trap and acquire green technology financing. By comparing different established entrepreneurial firms during the process to acquire financing, the research examined the GTFS contextual influence on the deployment of competencies, revealing the multi-faceted nature of the competency trap. In order to acquire GTFS financing the research identified two sets of entrepreneurial necessary competencies; (i) opportunity refinement competencies (ii) resource acquisition competencies. However, development of these competencies is influenced by the established entrepreneurial firms’ paths and the competency trap. Four different pathways to address the competency trap are highlighted. This emphasizes the need for more contextual based research at multiple levels of analysis to understand established entrepreneurial firms’ transition into sustainable entrepreneurship ventures.